1998
DOI: 10.1086/514232
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Two Efficacious Outer Membrane Protein‐Based Serogroup B Meningococcal Vaccines among Young Adults in Iceland

Abstract: Serum bactericidal activity (SBA) and ELISA antibody levels elicited by two efficacious serogroup B meningococcal vaccines were measured in a controlled trial involving 408 15- to 20-year-olds. Subjects were given two doses at a 6-week interval of a serogroup B or control vaccine. Response was defined as > or = 4-fold rise in antibody level. After two doses of the Finlay Institute (Havana) vaccine at 12 months, the proportions of SBA and ELISA responders were not different from those of the control group (15% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
116
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 11 publications
8
116
0
Order By: Relevance
“…Three studies have examined the effect of MenB OMV vaccines on carriage; in Chile [77], Norway [78] and Iceland [79], high vaccine coverage had no effect on rates of meningococcal carriage. A large study in the UK of nearly 3000 young adults immunized with 4CMenB and/or quadravalent meningococcal A, C, W135, Y conjugate vaccines is examining the effect on rates of meningococcal carriage [104].…”
Section: Carriage and Herd Immunitymentioning
confidence: 99%
“…Three studies have examined the effect of MenB OMV vaccines on carriage; in Chile [77], Norway [78] and Iceland [79], high vaccine coverage had no effect on rates of meningococcal carriage. A large study in the UK of nearly 3000 young adults immunized with 4CMenB and/or quadravalent meningococcal A, C, W135, Y conjugate vaccines is examining the effect on rates of meningococcal carriage [104].…”
Section: Carriage and Herd Immunitymentioning
confidence: 99%
“…The Men-B vaccines that have been most extensively investigated in human clinical trials are based on multiple subcapsular surface Ags in which porin A (PorA), a class 1 outer membrane protein (OMP), appears to be a dominant immunogen (20 -24). These include two partially purified Men-B OMP vaccines, developed by the Finlay Institute in Cuba and the National Institute of Public Health in Norway, that are presented as proteoliposome vesicles adsorbed onto aluminum hydroxide (21,22,25), and an outer membrane vesicle (OMV) hexavalent vaccine developed at the Netherlands Institute of Public Health and the Environment (Rijksinstituut voor Volksgezondheid & Milieu), derived from two recombinant strains each expressing three different PorA proteins (23). Although these vaccines have been shown to engender a 50 -80% protective efficacy, this has frequently been found to be strain specific, variable in infants under 18 mo of age, and of limited longevity (20).…”
mentioning
confidence: 99%
“…Depending on the nature of the T cell help, contact with Ag at a mucosal surface can either lead to a predominantly proinflammatory Th1-type response, an Ab-associated Th2 response (29), or, in the absence of danger signal, tolerance (31,32). It is unclear whether meningococcal carriage results in immunological priming or immune unresponsiveness, as with microbial colonizers at other mucosal sites and to what extent mucosal cellular immunity accounts for the disparity between the levels of SBA and protective immunity observed in vaccine trials (22,33) In this study, we aimed to ascertain whether T cell-mediated immunological memory to N. meningitidis is located at the mucosal level, to characterize the nature of this response, and to determine its relationship to circulating humoral immunity.…”
mentioning
confidence: 99%
“…Experimental OMV vaccines have undergone phase III trials in humans (3,4,11,31) and have been shown to produce limited protection in adults (3). However, the immune responses were of limited duration (32), and no protection was shown in children under 2 years of age, the group at greatest risk of infection (11,28).…”
mentioning
confidence: 99%